Effect of sintering temperature on mechanical properties and microstructure of zeolite (clinoptilolite) reinforced bovine hydroxyapatite (BHA) composites - (:unkn) unknown (CRC PRESS-TAYLOR & FRANCIS GROUP, 2010)
The applications of ceramics of pure hydroxyapatite (HA), which are nowadays restricted to non-load bearing implants due to the poor mechanical properties of HA, can be expanded via doping of HA-matrix with biocompatible (or even better bioactive) oxides resulting in strong HA-composites. In this study, we have doped biologically derived apatite from bovine bones (BHA) with 5 wt% and 10 wt% zeolite, clinoptilolite, which is a very pure form of zeolite, and being currently widely used in drug manufacturing industry, in poultry (for getting eggs with better properties) and feeding ingredient for cows for getting high quality milk. The HA-zeolite composites were produced via regular sintering technique, whereby clinoptilolite was used considering to serve as a wetting agent of HA particles. The compression strength and the microhardness of produced composites were measured as 127.7 MPa for 10% zeolite addition and sintering at 1200 degrees C, and 431 HV for 10% zeolite addition and sintering at 1300 degrees C.
Keywords: COMMERCIAL INERT GLASS; BONE; COATINGS; CELLS